Indonesian Undergraduate EFL Students’ Perceptions toward Flipped Classroom - Amanda Vira Maharani; Hamamah; Ika Nurhayani (Edcomtech: Jurnal Kajian Teknologi Pendidikan, 2020)
The aim of this study was to find Indonesian undergraduate EFL students’ perceptions towards the implementation of flipped classroom. This study implemented survey research design and perceptions were found out through questionnaire and the questionnaires were spread to 30 students who experienced the implementation of flipped classroom. The questionnaire consisted of two aspects, namely meaningful and competence aspects. The results of questionnaire of perceptions were statistically calculated. The data on meaningful aspect revealed that mostly the students had positive perceptions toward the implementation of flipped classroom. On the other hand, in competence aspect, the students perceived that flipped classroom was beneficial for their writing competence. However, for the pre-class activities, such as viewing video and reading e-materials, the students had varied perceptions on it. They actually like the idea to have an additional video-lecture and e-material to prepare them before the class, but they did not really see the meaning by doing that pre-class activities.